Investigating EFL students’ interest in the use of online discussion technique in asynchronous learning - Indah Zezarwati; Andi Kaharuddin; Multazam Abubakar; Muhammad Syahruddin Nawir (Journal of Applied Studies in Language, 2022)
The development of the era can be inextricably linked to the development of technology as it has entered all aspects of human life, including education. One of the technology utilization in education is e-learning which allows the learning process can be accessed anytime and anywhere. One technique commonly used in asynchronous learning nowadays is online discussion. This research aims at investigating the level of students’ interest and the factors that affect their interest in the implementation of the online discussion techniques. This research was conducted by mix-method, where the data was collected from the questionnaire and interview. The subjects of this research were 40 students in the questionnaire section and 4 students in the interview section. The result of the interview proved that students had a high interest in the implementation of online discussion techniques; while, the result of the interview indicated some factors that affect students’ interest in the implementation of online discussion techniques such as teacher activeness and involvement, internet connection, students’ motivation and concentration. Hopefully, this research can help to maximize the application of online discussion techniques to gain more benefits in the learning process.